2006
DOI: 10.1063/1.2360203
|View full text |Cite
|
Sign up to set email alerts
|

Strong configurational dependence of elastic properties for a binary model metallic glass

Abstract: In this work, the strong dependence of elastic properties on configurational changes in a Cu-Zr binary metallic glass assessed by molecular dynamics simulations is reported. By directly evaluating the temperature dependence and configurational potential energy dependence of elastic constants, the shear modulus dependence on the specific configurational inherent state of metallic glasses is shown to be much stronger than the dependence on Debye-Grüneisen thermal expansion. © 2006 American Institute of Physics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…29 Also, the quench rate in Ref. 24 was approximately ten times higher than in our work, which could also have an effect due to configurational relaxation differences. It is interesting to note that for our Cu 64.5 Zr 35.5 metallic glass, the calculated Poisson's ratio for the supercooled liquid is a little higher than 0.5 and the shear modulus is slightly negative.…”
Section: A Temperature Dependence Of Elastic Propertiescontrasting
confidence: 40%
See 2 more Smart Citations
“…29 Also, the quench rate in Ref. 24 was approximately ten times higher than in our work, which could also have an effect due to configurational relaxation differences. It is interesting to note that for our Cu 64.5 Zr 35.5 metallic glass, the calculated Poisson's ratio for the supercooled liquid is a little higher than 0.5 and the shear modulus is slightly negative.…”
Section: A Temperature Dependence Of Elastic Propertiescontrasting
confidence: 40%
“…Using this approach, we find that the temperature dependences of the Poisson's ratio and shear modulus ͑Fig. 3͒ clearly display a transition between the amorphous solid to the supercooled liquid at T ϳ 1000 K. Note that Duan et al 24 performed MD simulations on a metallic glass richer in Zr, Zr 54 Cu 46 and found comparable decreases in bulk and shear moduli with increasing temperatures below T g . Between 300 and 500 K, the values of these two elastic constants are considerably higher in the Cu 64.5 Zr 35.5 alloy examined in our study.…”
Section: A Temperature Dependence Of Elastic Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…More precisely, G was found to be a unique decreasing function of h independent of whether h is induced by thermal excitation or mechanical deformation [11,15]. This decreasing dependence of G on h reflects the decreasing curvature of the potential energy density function with increasing configurational energy and has been validated computationally [17]. In the inset in Fig.…”
Section: Prl 99 135502 (2007) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 88%
“…This compositional complexity makes it extremely difficult for different atoms to rearrange their spatial positions so that they are frozen directly into a disordered glassy structure upon cooling. Recently, binary BMG forming alloys have also been developed in a few alloy families [6][7][8][9][10][11][12][13][14], and their GFA is found to be very sensitive to the minor change of chemical composition [15,16]. These further confuse the criterions of GFA in metallic alloys.…”
Section: Introductionmentioning
confidence: 94%